Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations slowly, you would put water-drinking at the head of your list of things to do to become attractive. Your body is largely made of water, and three or four glasses a day is not too much if you want to avoid becoming sallow. Business girls are apt to suffer from indigestion and scragginess and "nervous" headaches, because they go from breakfast to supper with only a small cup of afternoon tea. Water is not always handy on business premises, though it ought to be. Take a glassful before you go to bed and when you rise in the morning. Half an orange or lemon or a few fresh raisins standing in the glass overnight will keep your inside clean and in good working order. A CLEAR COMPLEXION Should a girl make up? Well, that depends on what you mean by make-up! If you mean rouge and liquid powder, blue eyelids and blackened lashes — certainly not! Such make-up shows dreadfully — far worse than your mirror leads you to believe — and is both vulgar and unbecoming. A little pure powder does no harm if put on lightly, but do not keep on powdering because your face looks as if it wanted a wash! Repeated powdering clogs up the pores and is bad for any skin. If you must use powder, at least wash it off before beginning again, and do, please, use a clean powder-puff or the corner of a clean handkerchief. Healthy girls have such velvety complexions, yet so many completely ruin them by make up. When you are young it is a pity to put such a strain on your skin. [illustration] 16 177/5/8/4